Sjögren's syndrome at the crossroad of polyautoimmunity (2012)
The coexistence of autoimmune diseases (i.e., polyautoimmunity) in Sjögren's syndrome (SS) was investigated in a cross-sectional study involving 410 patients. Logistic regression analysis and the Rogers and Tanimoto index were used to evaluate risk factors and clustering, respectively. There were 134 (32.6%) patients with polyautoimmunity. The most frequent and closer coexistent diseases were autoimmune thyroid disease (21.5%), rheumatoid arthritis (8.3%), systemic lupus erythematosus (7.6%), and inflammatory bowel disease (0.7%) which together constituted a cluster group. There were 35 (8.5%) patients with multiple autoimmune syndrome. Besides disease duration, a history of habitual smoking and spontaneous abortion were found to be risk factors for the developing of polyautoimmunity. This study discloses a high prevalence of polyautoimmunity in SS, its associated risk factors and the grouping pattern of such a condition. These results may serve to define plausible approaches to study the common mechanisms of autoimmune diseases. © 2012 Elsevier Ltd.